Detection of Plasmopara halstedii in sunflower seeds: A case study using molecular testing - Martínez, Ana Laura (2021)
Plasmopara halstedii (Farl.) Berl. & De Toni causing downy mildew of sunflower is responsible for considerable economic losses worldwide. Because P. halstedii can be seed-transmitted, monitoring of seeds for pathogen contamination is important for the sunflower seed trade. The relevance of asymptomatic or latent infections as factors of disease spread have not been studied by molecular techniques. A molecular marker based on a putative effector gene of P. halstedii was used to examine the pathogen´s presence in asymptomatic sunflowers growing near patches of mildewed plants in naturally infected fields. The method based on conventional PCR was highly sensitive for detection of P. halstedii in DNA from whole seeds. By the application of this protocol, we found that all seed samples obtained from symptomatic plants amplified the expected fragment, whereas the diagnostic marker identified the presence of pathogen in one out of 21 asymptomatic plants. Possible uses of this marker to detect downy mildew in seed from asymptomatic plants or for race identification are discussed.